BARRIERS AND PROSPECTS OF LMS APPLICATION IN ISLAMIC HIGHER EDUCATION - Nur, Nur Aliyah; Aminah, Aminah; Amir, Reski; Ardin, Hardiani (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
The study aimed at finding out the students' access and ease with technology, as well as the barriers and prospects of using the Learning Management System (LMS) at Institut Parahikma Indonesia (IPI). An explanatory sequential mixed method was used in this study. There were 16 students from English Education Department and four lecturers selected using the purposive sampling technique. The instruments were a questionnaire and an in-depth interview. The results revealed that the students' access was well-versed in technology and felt at ease utilizing the LMS. Students' and lecturers' common barriers were insufficient bandwidth connections and a lack of personal time management, while their common prospects were enhanced infrastructure and internet connections, and large capacity in LMS for uploading data, lack of training for students, incompatible features in particular assignments, and a limited budget for internet usage. Meanwhile, students' prospects were LMS application on Google Play, direct assignment notification via SMS, and feedback from lecturers. In contrast, the lecturers' prospects were that all IPI materials should be accessible in LMS. Therefore, the institution needs to provide LMS training for the students, evaluate the lecturers, and enhance the capacity of the bandwidth connection. Moreover, the LMS features should be upgraded to maximize the functions. Abstrak: Penelitian ini bertujuan untuk mengetahui akses dan kemudahan mahasiswa terhadap teknologi, serta hambatan dan prospek penggunaan Learning Management System (LMS) di Institut Parahikma Indonesia (IPI). Metode campuran sekuensial penjelas digunakan dalam penelitian ini. Ada 16 mahasiswa dari Jurusan Pendidikan Bahasa Inggris dan empat dosen yang dipilih menggunakan teknik purposive sampling. Instrumen yang digunakan adalah angket dan wawancara mendalam. Hasil penelitian menunjukkan bahwa akses siswa fasih dalam teknologi dan merasa nyaman memanfaatkan LMS. Hambatan umum mahasiswa dan dosen adalah koneksi bandwidth yang tidak mencukupi dan kurangnya manajemen waktu pribadi, sementara prospek umum mereka adalah peningkatan infrastruktur dan koneksi internet, dan kapasitas besar di LMS untuk mengunggah data, kurangnya pelatihan untuk mahasiswa, fitur yang tidak kompatibel dalam tugas tertentu , dan anggaran terbatas untuk penggunaan internet. Sedangkan prospek mahasiswa adalah aplikasi LMS di Google Play, notifikasi tugas langsung melalui SMS, dan feedback dari dosen. Sebaliknya, prospek dosen adalah bahwa semua materi IPI harus dapat diakses di LMS. Oleh karena itu, institusi perlu memberikan pelatihan LMS kepada mahasiswa, mengevaluasi dosen, dan meningkatkan kapasitas koneksi bandwidth. Selain itu, fitur LMS harus ditingkatkan untuk memaksimalkan fungsi.